ASM Handbook. Volume 12, (American Society for Metals., 1987)
ASM Handbook, Volume 12 provides engineers with enhanced capability for recognizing and interpreting the various features of a fracture, enabling performance of improved failure analyses and ability to better determine the relationship of the fracture mode to the microstructure. The Atlas of Fractographs, which comprises the second half of the volume, contains over 1,300 fractographs that are invaluable for understanding the causes and mechanisms of the fracture of engineering materials. In addition to a comprehensive collection of fractographs of ferrous and nonferrous alloy parts and test specimens, supplemental illustrations of failed metal-matrix composites, resin-matrix composites, polymers, and electronic materials are included. This volumes provides sections on preparation and preservation of fracture specimens, photography of fractured parts and fracture surfaces, visual examination and light microscopy, scanning electron microscopy, transmission electron microscopy, quantitative fractography, and fractal analysis of fracture surfaces -- publisher.